Challenges in Burns Management in a Tertiary Care Center in Albania - Vladimir Filaj; Ester Tabaku; Ina Kola; Ferdiola Gjonaj; Vilma Tafilaj; Henri Drinjak (Albanian Journal of Trauma and Emergency Surgery)
Introduction: Burn injuries represent a significant public health concern globally, with a substantial impact on morbidity and mortality rates, particularly in low- and middle-income countries.